Is scaling plasma technology for per- and polyfluoroalkyl substances removal from leachate worthwhile: Life cycle assessment perspective - Dobril Valchev; Irina Ribarova; Elisa Blumenthal; Massimiliano Sgroi (Results in Engineering)
Landfill leachate is a primary source of per- and polyfluoroalkyl substances (PFAS) contamination in the environment. Non-thermal plasma (NTP) treatment has demonstrated promising results in terms of PFAS destruction; however, challenges related to scalability, cost, and environmental impact assessment persist. This study conducts a Life Cycle Assessment (LCA) to evaluate the environmental performance of NTP-based technology and its potential for scaling up, based on published laboratory-scale data. Furthermore, a comparison has been made between NTP technology and traditional evaporation and incineration for PFAS removal. Sofia Landfill's leachate treatment facility in Bulgaria served as a case study. The site's leachate treatment facility currently incorporates conventional mechanical and biological treatment processes, with a reverse osmosis (RO) system being planned as a future final step. Three alternatives were evaluated: 1) A1-RO1/P involves the application of plasma treatment to the RO concentrate; 2) A2-RO2/P includes a second-stage RO system with plasma treatment for its concentrate; and 3) A3-RO2/E comprises of a second-stage RO system with concentrate evaporation and off-site incineration of its sludge. The LCA has identified human toxicity potential, freshwater and marine ecotoxicity, freshwater eutrophication and global warming potential as the five key impact categories. The analysis indicates that Bulgaria's electricity mix was the primary impact contributor, followed by transportation. The plasma-based alternatives demonstrated superior performance over the evaporation-incineration alternative, with A2-RO2/P achieving the lowest normalized environmental impact. However, pilot experiments are needed to validate these conclusions. Moreover, the expansion of LCA databases is imperative to enhance the evaluation of PFAS's environmental implications.